Towards global elimination of Trachoma: An evaluation of Trachoma surveillance system, Wa East District, Ghana - Ernest Akyereko; Donne Kofi Ameme; Edwin Andrew Afari; Kofi Mensah Nyarko; Samuel Sackey; Delia Akosua Benewah Bandoh; Ernest Kenu (Journal of Interventional Epidemiology and Public Health)
Introduction: Trachoma is leading cause of preventable blindness globally with the highest prevalence in Africa (85% of global cases). In Ghana, Upper West and Northern Regions are endemic for trachoma. Ghana has made significant strides toward the global elimination of trachoma (GET) 2020 target and reported to have reached the initial elimination thresholds of 5.0% for trachomatous inflammation-follicular (TF) among children 1 to 9-years old. We evaluated the Trachoma surveillance system in the Wa East district in Upper West region to determine its performance, usefulness and assess the system attributes.